Analysis of Biological Factors Associated with Preeclampsia in Pregnant Women - Nanik Yuliwati; Siti Juhariyah; Irmala Dewi; Irma Yuliawati; Ika Sartika Dewi (Jurnal Penelitian Pendidikan IPA, 2024)
Preeclampsia is a serious complication during pregnancy that poses significant health risks to both mother and fetus, potentially leading to death. Early identification of biological factors associated with preeclampsia is crucial for effective prevention. This study aims to analyze the biological factors influencing preeclampsia incidence among pregnant women. A quantitative design with a case-control approach was used, focusing on pregnant women with a history of preeclampsia in the Curug Community Health Center, Karawang Regency. The sample included 10 respondents. The results revealed a significant relationship between parity and preeclampsia incidence (p-value 0.031), BMI (p-value 0.018), diet (p-value 0.041), and history of complications (p-value 0.001). However, no significant association was found between lifestyle activities and preeclampsia (p-value 0.114). These findings suggest that factors like parity, BMI, diet, and complications history are significantly linked to preeclampsia incidence. These results provide a basis for targeted interventions in pregnant women's care. Future studies should expand the sample size and consider additional variables such as employment status, family support, and stress levels for more comprehensive insights into preeclampsia risk factors.